THE U.S. QUEST FOR NEW TECHOLOGICAL FOUNDATIONS OF MILITARY SUPERIORITY: DILEMMAS OF THE THIRD OFFSET STRATEGY - V. I. Bartenev (Vestnik MGIMO-Universiteta)
The last decades have witnessed a remarkable surge of interest in studying the influence of science and technology on world politics. However, not all channels of such influence have been examined with equal rigor. Whereas numerous researchers have explored meticulously the impact of technologies on warfare, the issues of using military-technological breakthroughs to achieve political goals have been addressed less frequently. This paper seeks to fill this gaping niche by decomposing the Third Offset Strategy (TOS), a recent initiative of the U.S. Department of Defense (DoD) aimed at ensuring military-technological superiority of the United States in the XXI century, predominantly, by offsetting the new capabilities of the Russian Federation and the Popular Republic of China. The first section unveils a conceptual framing of the TOS, the second section examines a variety of technological priorities, and the final section identifies key uncertainties around implementation of this initiative in the mid-term and long-term perspective. The conclusion postulates that the emergence of the TOS was determined by both an erosion of the U.S. military superiority and budget constraints, and, therefore, its content might change if budget austerity imperatives will stop dominating the DoD strategists' thinking. The launch of the third offset strategy has also important international-political aspects. First, the TOS fits in the context of the U.S. rebalance to the Asia-Pacific. Second, the American allies in Europe might face a threat of a widening technological gap with the United States and a need to boost their spending on defense research and development, which might be unfeasible in the current fiscal environment. Third, the concentration of the United States on countering high-end opponents might lead to a further marginalization of the Middle East. Fourth, the TOS is likely to contain a disinformation component and aim at dragging the peer competitors of the U.S. into an exhaustive arms race.